Ethyl ester/acyl hydrazide-based aromatic sulfonamides: facile synthesis, structural characterization, electrochemical measurements and theoretical studies as effective corrosion inhibitors for mild steel in 1.0 M HCl. Issue 1 (20th December 2022) - Bedair, Mahmoud A.; Abuelela, Ahmed M.; Alshareef, Mubark; Owda, Medhat; Eliwa, Essam M.
Abstract : Two new corrosion inhibitors were synthesized and applied to steel in 1.0 M HCl. The corrosion resistance was probed by electrochemical and theoretical methods. The study reveals significant intersections between electrochemical aspects and theory. Abstract : In this research paper, aromatic sulfonamide-derived ethyl ester ( p -TSAE ) and its acyl hydrazide ( p -TSAH ) were directly synthesized, characterized, and employed for the first time as prospective anticorrosive agents to protect mild steel in 1.0 M HCl conditions. The corrosion efficiency was probed by electrochemical methods including polarization, impedance, and frequency modulation measurements. Optimal efficiencies of 94% and 92% were detected for the hydrazide and ester, respectively, revealing excellent corrosion inhibition. Moreover, both the hydrazide and ester molecules combat the cathodic and anodic reactions correspondingly in a mixed-type manner. The electron transfer (ET) at the inhibitor/metal interface was evaluated using DFT at the B3LYP/6-31g(d, p) level. Natural bond orbital analysis (NBO) and frontier molecular orbital analysis (FMO) calculations showed superior capabilities of the synthesized inhibitors to easily reallocate charge into the metal surface. However, the hydrazide molecules showed slightly better inhibition efficiency than the ester due to the strong interaction between the lone pairs of the nitrogen atoms and the d-orbitals of the metal. The chemical hardness of the hydrazide and ester are 2.507 and 2.511 eV, respectively, in good accordance with the recorded electrochemical inhibition efficiencies for both molecules. Good and straightforward correlations between the experiments and calculations are obtained.